"Producing" Politics in Wag the Dog. (2nd January 2020) - Parrish, John
Abstract: Political philosophy has long worried about the blurred line between politics and entertainment. Plato famously held that democratic politics is highly susceptible to manipulation working through the art of storytelling and proposed banishing dramatists from his good society. More recently, some thinkers have focused on a different vulnerability: that ours is becoming a mass entertainment culture, increasingly shaped by a mass media amalgam of the artistic and commercial impulses. Yet, although many theorists have separately examined these dangers (storytelling and mass entertainment), attention has rarely been paid to the interaction effects between them. In this respect, we can learn from a close reading of the 1997 film Wag the Dog, which shows that the dangers to democratic politics of the storytelling art itself wind up being multiplied when they are transposed onto democratic politics in the context of mass entertainment society. This article argues that Wag the Dog offers a perceptive and far-sighted analysis of the changing nature of contemporary politics, and of how the forces of art, commerce, and manipulation combine in ways that transcend any single candidate or ideology, and which together serve to challenge – and perhaps to doom – our collective aspirations to genuine democratic self-governance.